An uncommon case of dual ventricular response in dual atrioventricular nodal non-reentrant tachycardia: A case report. Issue 23 (June 2018) - Zhang, Meiwei; Wang, Yeling; Chen, Dongmei; Li, Hang; Zhang, Zhiguo
Abstract: Rationale: Dual atrioventricular nodal non-reentrant tachycardia (DAVNNT) is an uncommon arrhythmia. Because of the different refractory periods of fast and slow pathways, a single atrial depolarization gives rise to 2 ventricular activationsthrough fast and slow pathways separately. Patient concerns: A 45-year-old woman was referred to our Cardiology Center with symptoms of recurrent palpitations and fatigue persisting for the previous 3 years. On echocardiography, the ejection fraction of the left ventricle was 45%. Diagnoses: Electrophysiological study findings and 12-lead electrocardiogram led to a diagnosis of DAVNNT. Interventions: Our case responded very well to the ablation of the slow pathway, and her tachycardia completely disappeared. Outcome: Her left ventricle ejection fraction also improved to52% after 3 months of follow-up. The patient remained asymptomatic throughout the follow-up period of 1 year, without any recurrence or complications. Lessons: DAVNNT is a rare arrhythmia which can induce tachycardia-induced cardiomyopathy. Ablation of the slow pathway isconsidered a curative treatment.